2014
DOI: 10.1017/jse.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Developing Social Skills of Students With Additional Needs Within the Context of the Australian Curriculum

Abstract: Decades of research on social skills assessment and intervention indicates the importance of social skills in improving academic achievement. Additionally, a strong evidence base promotes the inclusion of social–emotional learning into the whole school curriculum. In recognition of this evidence, the new Australian Curriculum, under Personal and social capability, calls for students to develop social skills. For many students with additional needs, it is hoped that the development of social skills will enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
0
24
0
7
Order By: Relevance
“…All students need to learn appropriate social skills (Agran et al, 2016;Davies., Cooper., Kettler., & Elliott, 2015;Lynch & Simpson, 2010;Rawles, 2016;Sanchez, Brown, & DeRosier, 2015;Yoder, 2015). In recent decades, in investigations of behavioral disorders and social deviations, sociologists and psychologists have found that many disorders have their roots in 1) individuals' inabilities to analyze themselves correctly and appropriately, 2) the lack of control and personal adequacy counter difficult positions, and 3) the lack of awareness to solve social difficulties and problems in an appropriate way (Zach, Yazdi-Ugav & Zeev, 2016 The study compares social skill components among students of ordinary schools and talented schools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All students need to learn appropriate social skills (Agran et al, 2016;Davies., Cooper., Kettler., & Elliott, 2015;Lynch & Simpson, 2010;Rawles, 2016;Sanchez, Brown, & DeRosier, 2015;Yoder, 2015). In recent decades, in investigations of behavioral disorders and social deviations, sociologists and psychologists have found that many disorders have their roots in 1) individuals' inabilities to analyze themselves correctly and appropriately, 2) the lack of control and personal adequacy counter difficult positions, and 3) the lack of awareness to solve social difficulties and problems in an appropriate way (Zach, Yazdi-Ugav & Zeev, 2016 The study compares social skill components among students of ordinary schools and talented schools.…”
Section: Resultsmentioning
confidence: 99%
“…The development of social skills lays a critical foundation for later academic achievement as well as work-related skills (Lynch & Simpson, 2010). Social skills are a collection of learned behaviors giving the individual the ability to have an influential relationship with others and to abstain from socially unreasonable reactions (Agran, Hughes, Thoma, & Scott, 2016;Davies, Cooper, Kettler http://dx.doi.org/10.15405/epsbs.2016.11.52 eISSN: 2357-1330 & Elliott, 2015;Gresham, 2016;Yoder, 2015). Cooperation, collaborating with the others, helping, initiating a relationship, requesting help, and praising and appreciating others are some examples of this type of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important educational aims is to develop social skills in students which are in turn expected to influence their personal, social and educational success (Morgan, Hsiao, Dobbins, Brown., & Lyons, 2015;Rawles, 2016). It is important that all students learn appropriate social skills (Agran et al, 2016;Davies, Cooper, Kettler & Elliott, 2015). Appropriate social skills provide opportunities and experiences that enable students to practice and apply social strategies and skills in actual environments and life situations (Chu & Zhang, 2015;Morgan et al, 2015).…”
Section: Building Competenciesmentioning
confidence: 99%
“…Children with social skills deficits may face psychological challenges in their present and later life. Previous research observed that the social skills' deficiencies will eventually lead to poor academic achievement, failed to achieve their social functioning, peer rejection, social withdrawal and isolation (Davies., Cooper., Kettler., & Elliott., 2014). Furthermore, children with social skills deficits are also more likely experiencing anxiety, depression (Welsh., Parke., Widaman., & O'Neil., 2001), and bullying (Garner & Hinton., 2010).…”
Section: Introductionmentioning
confidence: 99%